Analisis Wacana kritis Meme ‘Perilaku Mahasiswa di Kampus Bandung’ pada Akun Auto Base Twitter @bdgfess - Lestari, Martha Tri; Sabrina, Wilda Aula; Astuti, Sri Wahyuning (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2023)
ABSTRACT Memes as a form of virtual world communication have become increasingly widespread with a variety of purposes for making them, ranging from mere entertainment to criticizing social phenomena. This study aims to examine the humorous discourse contained in the meme 'Student Behavior on the Bandung Campus' at the macro and micro levels according to the theory of critical discourse analysis according to Teun A. van Dijk. The results of the study show that through text dimensions, the macro structure of the meme